2020
DOI: 10.1021/acssuschemeng.0c02819
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Selenium Nanoparticles on Celery Stimulates Several Nutrient Component Levels by Regulating the α-Linolenic Acid Pathway

Abstract: Selenium nanoparticles (SeNPs) show potential tendency in improving the plant health and food quality. However, the mechanism underlying SeNPs' capability to enhance the biosynthesis of more nutrient components such as flavonoids in crops remains unclear. In this study, it is found that foliar application of SeNPs on celery significantly enhanced the total antioxidant capacity, total flavonoids, total phenols, and vitamin C levels of celery leaves by 46.7, 50.0, 21.4, and 26.7%, respectively. The SeNP applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 43 publications
(78 reference statements)
1
36
0
1
Order By: Relevance
“…Recently, polyphenols have received the attention of scientists and consumers, due to their potential medicinal properties in the prevention and cure of various degenerative diseases, particularly cancers, cardiovascular diseases and neurodegenerative diseases [81]. Li et al [76] found that foliar application of 5 mg/L of selenium (Se) NPs in celery enhanced the total antioxidant capacity (46.7%), total flavonoids (50%), such as apigenin, p-coumaric acid, ferulic acid, luteolin and kaempferol, total phenols (21.4%) and vitamin C (26.7%). Furthermore, a synergistic effect between NPs and other types of compounds has been demonstrated.…”
Section: Nutraceuticals and Nutritional Compounds Induction Using Npsmentioning
confidence: 99%
“…Recently, polyphenols have received the attention of scientists and consumers, due to their potential medicinal properties in the prevention and cure of various degenerative diseases, particularly cancers, cardiovascular diseases and neurodegenerative diseases [81]. Li et al [76] found that foliar application of 5 mg/L of selenium (Se) NPs in celery enhanced the total antioxidant capacity (46.7%), total flavonoids (50%), such as apigenin, p-coumaric acid, ferulic acid, luteolin and kaempferol, total phenols (21.4%) and vitamin C (26.7%). Furthermore, a synergistic effect between NPs and other types of compounds has been demonstrated.…”
Section: Nutraceuticals and Nutritional Compounds Induction Using Npsmentioning
confidence: 99%
“…Se (0, 0.2, and 1 mg/L) and Cd (0 and 1 mg/L) were added to the vessel in form of Cd 2+ in water/medium: 5% nitric acid (1000 mg/L) and nano-Se. The nano-Se was characterized as previously described [ 21 ]. The experiment was established with five repetitions of the six treatments that included Cd0Se0, Cd0Se0.2, Cd0Se1, Cd1Se0, Cd1Se0.2, and Cd1Se1.…”
Section: Methodsmentioning
confidence: 99%
“…Four-week-old Arabidopsis and 2-week GhPLP2 -silenced cotton plants after VIGS were used to analyze the composition of fatty acids and quantify the hormones. The hormones were quantified as previously described ( Li D. et al, 2020 ). Fresh samples were ground into fine powder in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…MS was performed using the multiple reaction monitoring modes and negative electrospray ionization. All the parameters were performed as described by Li D. et al (2020) .…”
Section: Methodsmentioning
confidence: 99%